2009
DOI: 10.1080/01480540802588485
|View full text |Cite
|
Sign up to set email alerts
|

A new illicit opioid dependence outbreak, evidence for a combination of opioids and steroids

Abstract: Opioid abuse is common in Iran. In 2005, a new version of locally produced illicit opioid vials, so called Norgesic, appeared in the illicit market, which gained popularity rapidly and led to an improvement of stigmatizing the general appearance of dependent cases. Later, some cases suffered Cushing's-like problems. A prospective case series was designed to evaluate 18 Norgesic-dependent subjects who volunteered for abstinence therapy in a rehabilitation clinic from November 1, 2005, to December 30, 2005. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Opioid dependency, overdose, and related complications are common in Iran in various age groups and gender [6,7]. In recent years, tramadol overdose has become one of the most common causes of poisoning admissions to emergency departments in this country [5,[8][9][10]].…”
Section: Introductionmentioning
confidence: 99%
“…Opioid dependency, overdose, and related complications are common in Iran in various age groups and gender [6,7]. In recent years, tramadol overdose has become one of the most common causes of poisoning admissions to emergency departments in this country [5,[8][9][10]].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic and musculoskeletal complications of Temgesic abuse imposed a heavy burden on the healthcare system in the recent years (4,5). This drug has been widely abused as a result of its low cost and its ability to mask the typical malnourished appearance of opium-dependent patients.…”
Section: Discussionmentioning
confidence: 99%
“…Temgesic vials contain corticosteroids and almost all abusers have signs of hypercortisolism, such as striae on their abdominal skin (4). Biochemical studies revealed that the available product in Iran consists of diacetylmorphine, acetylcodeine, pheniramine and heroin (4,5,15). As each vial contains 0.4mg Dexamethasone (4), patients of the present study had received an average of 767 mg (ranged 299 to 1792) Dexamethasone by the time of pain onset, which is equivalent to 5061 mg (ranged 1973 to 11827) of prednisone (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was well known that continual use of opioids could result in the tolerance and dependence of opioids (Koushesh et al, 2009). Prenatal exposure to opiates can have devastating effects on the development of human fetuses (Slamberová et al, 2005).…”
Section: Introductionmentioning
confidence: 99%